Nilai Prestasi sebagai Moderator Hubungan Kegigihan dengan Prestasi Akademik - Azka Ananda Sari; Lucia R. M. Royanto (Jurnal Psikologi Teori dan Terapan, 2019)
Value is a fundamental variable that underlies human life. Value serves as a guidance for someone to take an action. In the field of education, achievement value orientation can guide a students to act accordingly in order to gain academic achievements. The aim of this study was toexamine how achievement value serve as a moderator bewtween grit and academic achievement relations. Data were collected using online surveys from 363 undergraduate students of University of Indonesia and were analyzed using multiple regression. The results show that achievement value is significantly proved as a moderator of the relationship between grit and academic achievement. Students who believe in a greater achievement value shows grittier behavior in the context of study and greater effort in facing challenges in college. The grittier the students, the higher academic achievementsthey achieve.Keywords: Achievement value, grit, academic achievement, students